THE EFFECT OF INFRARED RAY AND COUNSELING ON DIABETIC FOOT ULCER HEALING PROCESS - Mokh Sujarwadi; Mukhammad Toha; Nurul Huda (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Diabetic foot ulcer is one of the chronic complications of diabetes mellitus caused by neuropathy, angiopathy and decreased endurance. The risk of amputation in patient with diabetes mellitus fifteen times greater compared to non-diabetic. Various efforts on diabetic foot wound care have been carried out but the results are still far from satisfactory. Until now, infrared and counseling effect on wound healing in diabetic foot cannot be explained.Objective: The purpose of this study was to examine the effect of infrared ray and counseling on diabetic foot ulcer healing process.Method: The research design was quasi-experimental design with posttest control group design, the population in this study were patients with grade 3 diabetic foot wounds, blood sugar 100-200 g/ dl, BMI 18.5 to 24.9, aged 35-55 years. Large sample in this study as many as 20 were divided into two groups, the control random sampling. The collection of data for the dependent variable using the observation sheet after the tenth day of treatment, which consists of the rate of growth of granulation, ankle brachial index and capillary refill time. Furthermore, the data were processed using non-parametric statistical significance level < 0.05.Result: The results showed that the infrared and counseling effect on the growth of granulation with a significance level (p = 0.0003), infrared and counseling influence ankle brachial index (p = 0.024), infrared and counseling effect on capillary and counseling effect on capillary refill time (p = 0.024).Conclusion: It can be concluded from this study that applying infrared and counseling has any impact on healing in diabetic foot ulcer, on the growth of granulation and improved blood in diabetic foot ulcers. Key words: Infrared Ray, Counseling, Foot Ulcer Healing.